Modification of Fresh-Water Clamshells (Pilsbryoconcha exilis compressa) as New Raw Material and its Application in the Biodiesel Production of Lard Oil - Moonsin, Preecha; Roschat, Wuttichai; Phewphong, Sunti; Leelatam, Tappagorn; Namwongsa, Krittiyanee; Thangthong, Amonrat; Panyakom, Sirin; Yoosuk, Boonyawan; Promarak, Vinich (Trends in Sciences, 2023)
In the present work, the catalytic activity and stability of the Fresh-water Clamshells-derived CaO catalyst were investigated by the transesterification reaction of lard oil. The physicochemical properties of lard oil as a raw material for biodiesel production compared with palm oil were also studied. The obtained CaO_FWC was characterized by various analytical techniques to evaluate the physicochemical properties consisting of TGA, SEM, XRD, XRF, BET surface area, FT-IR, Hammett indicator method, and CO2-TPD. The results found that the fresh CaO_FWC showed the specific surface area, percentage of Ca element, total basic site, and basic strength of 8.293 m2g−1, 98.6 wt.%, 8.450 mmol g−1, and 15 < H_< 18.4, respectively which similar to CaO commercial grade. In addition, the fresh CaO_FWC catalyst also presented high catalytic activity that gave %FAME of lard oil more than 96.5 %. However, the CaO_FWC catalyst could only reuse 3 times with the catalytic activity slightly decreased, and %FAME remained higher than 95 %. While the stability of the CaO_FWC catalyst was tested by storage for a long time to 180 days, this experimental data suggested that the CaO_FWC catalyst could preserve for only 30 days, with the catalytic efficiency remaining similar to the fresh CaO_FWC. Furthermore, the preservation and reusability of the catalyst were also studied in terms of the kinetic rate of reaction for use as a database to optimize the reaction conditions. Finally, the fuel properties of biodiesel products derived from lard oil and palm oil as raw materials and catalyzed by CaO_FWC catalyst met the specified standards both of EN-14214 and ASTM-D6751. Therefore, all the results of this work were excellent databases for utilizing and adding value to the Fresh-water Clamshells and lard oil as biomass sources for further development and development as renewable and alternative energy in Thailand. HIGHLIGHTS The CaO catalyst obtained after calcination of the Fresh-water Clamshells has displayed excellent catalytic activity for the transesterification of lard oil with biodiesel conversion and FAME yield obtained under optimal conditions up to 96.86 % The Fresh-water Clamshells could stand promising resource for low-cost catalysts to lead the way for low-cost biodiesel The kinetic data can be used to optimize the biodiesel production process GRAPHICAL ABSTRACT